2012
DOI: 10.1021/jp305273n
|View full text |Cite
|
Sign up to set email alerts
|

PNP Equations with Steric Effects: A Model of Ion Flow through Channels

Abstract: The flow of current through an ionic channel is studied using the energetic variational approach of Liu applied to the primitive (implicit solvent) model of ionic solutions. This approach allows the derivation of self-consistent (Euler-Lagrange) equations to describe the flow of spheres through channels. The partial differential equations derived involve the global interactions of the spheres and are replaced here with a local approximation that we call steric PNP (Poisson-Nernst-Planck) (Lin, T. C.; Eisenberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
184
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(186 citation statements)
references
References 258 publications
0
184
0
Order By: Relevance
“…It is essentially a system coupling diffusion and electrostatics, and the nonlinearity comes from the drift effect of electric field on ions. Such a system and its variants have found extensive and successful applications in biological systems, in particular in the description of ion transport through cells and ion channels [1,2]. It has also been applied to many industrial fields, such as the semiconductor devices [3] and the detection of poisonous lead by ion-selective electrode [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essentially a system coupling diffusion and electrostatics, and the nonlinearity comes from the drift effect of electric field on ions. Such a system and its variants have found extensive and successful applications in biological systems, in particular in the description of ion transport through cells and ion channels [1,2]. It has also been applied to many industrial fields, such as the semiconductor devices [3] and the detection of poisonous lead by ion-selective electrode [4].…”
Section: Introductionmentioning
confidence: 99%
“…Appendix A: The functions Fi, fi in Theorems 1,2 We show that the functions F i , f i are well defined. We take F i for example, and recall that…”
mentioning
confidence: 99%
“…There are a number of excellent works that have explored the e ects of nite ion size on transport (including PNP) [4,10,11,22,24,29,36,37,39,42,46]. The steric Poisson-Nernst-Planck [17] is one of typical models accounting for the nite-size e ects of ions formulated by the energetic variational approach [12]. It has been observed that the 1D computational results of steric Poisson-Nernst-Planck greatly enhances the selectivity of the ion channel.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the 1D computational results of steric Poisson-Nernst-Planck greatly enhances the selectivity of the ion channel. In the near future, another improvement of the Poisson-NernstBrought to you by | HEC Bibliotheque Maryriam ET J. Authenticated Download Date | 6/11/15 7:56 PM Planck model is to implement the 3D computations of steric Poisson-Nernst-Planck [17] taking into account the critical nite-size e ects of mobile ions moving through the narrow channel.…”
Section: Discussionmentioning
confidence: 99%
“…The differential capacitance plays an important role in modelling a wide variety of processes, such as the motion of colloidal particles in an applied electric field [1] and the behavior electro-osmotic pumps [2], including the phenomena of flow reversal in AC electro-osmosis [3], and the regulation of ion transfer and ion selectivity across cell membranes [4] and nanoporous channels [5,6]. It is relevant to the fields of biology, materials science, colloid science and the study of nano-fluidic devices.…”
Section: Introductionmentioning
confidence: 99%